Communication Strategy of Kudus Culture and Tourism in Introducing Religious Tourism to Foreign Tourists - Maharani, Anggi Putri; Rohimi, Primi (Ilomata International Journal of Social Science, 2025)
This study examines the communication strategies employed by the Kudus Culture and Tourism Office (Disbudpar) to promote religious tourism to international visitors. The research aims to analyze the effectiveness of these strategies in increasing Kudus' visibility as a religious tourism destination. A qualitative approach with a descriptive method was utilized, incorporating in-depth interviews, direct observations, and document analysis to gather insights from stakeholders, including Disbudpar officials, tour guides, and foreign tourists. The findings indicate that Disbudpar Kudus employs various promotional techniques, including social media campaigns, official websites, and participation in international tourism exhibitions. Social media platforms like Instagram and Facebook serve as primary channels, leveraging visual and interactive content to engage potential tourists. However, challenges remain, such as inconsistent responsiveness to inquiries and a lack of multilingual content. The study highlights the need for more immersive digital strategies to enhance engagement, such as augmented reality (AR) and virtual reality (VR). In conclusion, while the current strategies have contributed to increased international interest in Kudus, further improvements in digital engagement, global partnerships, and technological innovation are necessary to sustain long-term growth. This research provides practical recommendations for optimizing communication strategies to attract more international religious tourists and strengthen Kudus’ position in the global tourism market.